PLUPERFECT AUXILIARIES IN THE RUSSIAN LANGUAGE OF THE 14 th – 16 th CENTURIES - Anton V. Zimmerling (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2019)
This paper discusses the syntax of the past tense auxiliaries in the vernacular Old Russian plusperfect construction of the type дал был, дал есми был. I prove that the past tense auxiliaries behaved as enclitics both with the order дал есми был and with the order дал был есми. The order of the pluperfect auxiliaries reflects different types of a clitic template characteristic of late Old Russian dialects. In the 15 th century, the order <дал> есми был was characteristic for the official style of the Moscow charters, while Polotsk charters from the same period generalized the reversed order <дал> был есми. In the 16 th century, the order <дал> был есми has established in the Moscow official tradition as well. The pluperfect auxiliaries were excluded from the clause-initial position and other non-enclitic positions, sentences of the type *#был есмь дал ~ #был дал есмь are not attested. In the clause-internal position, both groups of the Old Russian dialects grammaticalized the fixed contact order of the auxiliaries #...был есми... дал ~ #дал был есми irrespective of the position of the verb. This distribution proves that the pluperfect auxiliaries in the Old Russian texts from the 14 th –16 th centuries have the features typical of the clustering enclitics in the world’s languages with Wackernagel’s law.